(untitled) (Regional aspects of productive forces development of Ukraine, 2022)
Introduction. The article clarifies the peculiarities of the formation of HR-analytics at the enterprise. The development of the personnel management system and the strengthening of competition both in the markets of goods and services and in the labor market require management to look for the latest approaches to improving efficiency. Goal. Substantiation of theoretical, methodological and practical recommendations for the formation of HR-analytics at the enterprise. Methods. The article uses methods of analysis and synthesis in the study of the concept of HR-analytics. Results. The concept of HR-analytics is relatively new in the personnel management system. The main task of this activity is to find the causes of inefficient use of staff and negative trends in its development and search for reserves to maximize the economic effect of the staff of the enterprise. Today HR-analytics is one of the most popular and priority areas in the field of organization, management, involvement and development of employees. Conclusions. HR-analytics is a system of information about the company’s staff, which is regularly collected and processed and on the basis of which the company’s management makes decisions or evaluates the effectiveness of previous decisions. HR-analytics involves the formation and analysis of information about the processes taking place in the organization and, on the basis of this analysis, to identify cause-and-effect relationships and dependencies between various characteristics, phenomena and processes, which will make it possible to develop effective management solutions aimed at overcoming negative trends development of the organization and ensuring its sustainable development.